The circumstances of the origin and history of the development of the church schism of the Belarusian diaspora in the first half of the 1980s - Slesarau, Aliaxandr V. (Journal of the Belarusian State University. History, 2020)
The article describes the history of the origin and development of the intra-confessional conflict that engulfed the Belarusian Autocephalous Orthodox Church (BAOC) in the first half of the 1980s. For the first time, a conclusion is drawn regarding the decisive role of the ideological prerequisites for the emergence of a split, rooted in the difference in approaches to understanding the principles of church governance. If the highest church leadership was characterised by a commitment to the ideas of the key role of hierarchy (clericalism), then representatives of parishes and Belarusian sociopolitical organisations insisted on the obligation to implement the principle of collegiality. The conflict developed as a result of the structural and administrative division of the BAOC, mutual compromise of opponents, a significant reduction in the financial possibilities of parishes and the disintegration of the Belarusian diaspora. Unlike the Ukrainian Autocephalous Orthodox Church in exile, divided and weakened by internal contradictions, the BAOC was unable to expand its activities in Belarus in the late 1980s and 1990s.
Keywords: autocephaly; Belarusian diaspora; Belarusian Autocephalous Orthodox Church; Belarusian People’s Republic; emigration; Orthodoxy; Orthodox Church